Determination of strength and debonding energy of a glass-concrete interface for encapsulation-based self-healing concrete. (May 2017) - Gilabert, F.A.; Van Tittelboom, K.; Tsangouri, E.; Van Hemelrijck, D.; De Belie, N.; Van Paepegem, W.
Abstract: This paper presents a combined experimental-numerical analysis to assess the strength and fracture toughness of a glass-concrete interface. This interface is present in encapsulation-based self-healing concrete. There is absence of published results of these two properties, despite their important role in the correct working of this self-healing strategy. Two setups are used: uniaxial tensile tests to assess the bonding strength and four point bending tests to get the interfacial energy. The complementary numerical models for each setup are conducted using the finite element method. Two approaches are used: cohesive zone model to study the interface strength and the virtual crack closure technique to analyze the interfacial toughness. The models are validated and used to verify the experimental interpretations. It is found that a glass-concrete interface can develop a maximum strength of approximately 1 N/mm 2 with fracture energy of 0.011 J/m 2 .